Visualisasi Identitas Lokal dalam Komunikasi Grafis Studi Kasus Ampera Zam Zam - Fatin Putri Nusda; M. Nur Fahmi; Julia Delka Cahyani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Visual communication is very important for MSMEs in the restaurant sector because Help attract customers, build brand identity, and Convey information quickly. Increase Attractiveness. Design Attractive visuals, such as logos, menus, and restaurant interiors, can make Customers are more interested in coming and trying the food. To facilitate Information. Posters, infographics, and high-quality food images can Help customers understand the menu faster and evoke Their taste. Building Brand Identity. Consistent visual display, Including colours, fonts, and packaging designs, creating a professional impression and Help customers remember the restaurant. Strengthen The Promotion. Social media And marketing materials that use attractive visual designs can Increase engagement and attract more customers. Communication Effective visuals can be an important investment for MSMEs in the home sector Eat to increase competitiveness and attract more customers.